Keandalan Sistem Proteksi Kebakaran Pada Gedung (Studi Kasus : Hotel Pesonna Pekanbaru) - Ewis Oktareza; Rian Tri Komara Iriana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Pekanbaru, as capital city of Riau Province, has high economic growth, it can be seen from the development of high rise building. One of the new high rise building development in 2014 was Hotel Pesonna. The development of the building should consider safety aspects, one of them is fire safety. Thepurpose of this study is to evaluate and get the value of building reliability on fire hazard protection system Hotel Pesonna according to the Ministry of Public Works Regulation number 26, 2008. This study used checklist form Pd-T-11-2005-c (Fire Safety Inspection on Building) and the result from this form isused to get the reliability for fire hazard protection system using Analytical Hierarchy Process (AHP) method, then give recommendation for components in reliability for fire hazard protection system in building that have not met the requirements. There are four components of fire hazard protection systemconsidered in building, including completeness of site, means of rescue, active protection system, and passive protection system. The result of this study showed that the reliability of Hotel Pesonna on fire hazard protection system was in “Good” condition (B). The building reliability value calculated based onchecklist method and AHP method was 91.503 and 91.522 respectively. The difference between the two method is 1.9%, and several sub-component system that are listed in Ministry of Public Works Regulation number 26, 2008 (e.g completeness of site, means of rescue, and active protection system) should be fulfilled by the building owner.Keywords : Fire safety, reliability, Analytical Hierarchy Process (AHP)